Association of White Matter Hyperintensities With Short-Term Outcomes in Patients With Minor Cerebrovascular Events. Issue 4 (April 2018) - Zerna, Charlotte; Yu, Amy Y.X.; Modi, Jayesh; Patel, Shiel K.; Coulter, Jonathan I.; Smith, Eric E.; Coutts, Shelagh B.
Abstract : Background and Purpose—: White matter lesions (WML) are associated with cognitive decline, increased stroke risk, and disability in old age. We hypothesized that superimposed acute cerebrovascular occlusion on chronic preexisting injury (leukoaraiosis) leads to worse outcome after minor cerebrovascular event, both using quantitative (volumetric) and qualitative (Fazekas scale) assessment, as well as relative total brain volume. Methods—: WML volume assessment was performed in 425 patients with high-risk transient ischemic attack (TIA; motor/speech deficits >5 minutes) or minor strokes from the CATCH study (CT and MRI in the Triage of TIA and Minor Cerebrovascular Events to Identify High Risk Patients). Complete baseline characteristics and outcome assessment were available in 412 patients. Primary outcome was disability at 90 days, defined as modified Rankin Scale score of >1. Secondary outcomes were stroke progression, TIA recurrence, and stroke recurrence. Analysis was performed using descriptive statistics and regression models including interaction terms. Results—: Median age was 69 years, 39.8% were female. Sixty-two patients (15%) had unfavorable outcome with disability at 90 days (modified Rankin Scale score >1). Higher Fazekas scores were strongly correlated with higher WML volume ( r =0.79). Both higher Fazekas score and higher WMH volume were associated with disability at 90 days in univariate regression (odds ratio 1.22; 95% confidence interval, 1.04–1.43 and odds ratio, 1.25 per milliliter increase; 95% confidence interval, 1.02–1.54, respectively) but not with stroke progression, TIA recurrence, or stroke recurrence. In multivariable-adjusted analyses, additive interaction terms were associated with unfavorable outcome (adjusted odds ratio 3.99, 95% confidence interval, 1.87–8.49). Conclusions—: Our data suggest that quantitative and qualitative WML assessments are highly correlated and comparable in TIA/minor stroke patients. WML burden is associated with short-term outcome of patients with good prestroke function in the presence of intracranial stenosis/occlusion. Abstract : Supplemental Digital Content is available in the text.